2004
DOI: 10.1081/sei-120030392
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Studies of Lanthanide(III) Ions withN,N′‐Dimethyl‐N,N′‐diphenylpyridine‐2,6‐dicarboxyamide (DMDPhPDA) from Nitric Acid Solutions

Abstract: The new diamide compound, N,N 0 -dimethyl-N,N 0 -diphenylpyridine-2,6dicarboxyamide (DMDPhPDA), was synthesized and the distribution ratios of lanthanides from 1 to 5 M nitric acid solutions into DMDPhPDA CHCl 3 solution were determined. The extraction mechanism of lanthanide with DMDPhPDA was discussed based on the slope analysis of acid and ligand concentration dependencies and the variation of distribution ORDER REPRINTS ratio along the lanthanides series. The number of DMDPhPDA molecules in extracted compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…A number of extractants such as di-(-2-ethylhexyl) 2-ethylhexyl phosphonate (DEHEHP) [2][3][4], cyanex 923 [5][6][7][8], lueco xylene cyanol FF [9], 2-ethylhexyl hydrogen 2-ethylhexyl phosphonate (KSM-17) [10], N, N'-Dimethyl-N,N'-diphenylpyridine-2, 6-dicarboxyamide (DMDPhPDA) [11], N-phenylbenzo-18-crown-6-hydroxamic acid [12], 1-octyl-3-methylimidazolium hexafluorophosphate [13], high molecular weight carboxylic acids [14], N -phenyl -(1,2-methanofullerene C 60 ) 61-formohydroxamic acid [15], tri-nbutyl phosphate (TBP) [16], tridodecylamine (TDA), 1-[thenoyl- (2)]-3-3-3-trifluoroacetone (HTTA), di (2-ethylhexyl) phosphoric acid (HDEHP) and tricaprylmethylammonium chloride (TCMA) [17], calyx [4] resorcinarene-N-fenil-acetohydroxamic acid [18], have been used for the extraction and separation of Ce(IV). However, these methods have limitations such as interference of different ions, emulsion formation, co-extraction, and use of high reagent concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…A number of extractants such as di-(-2-ethylhexyl) 2-ethylhexyl phosphonate (DEHEHP) [2][3][4], cyanex 923 [5][6][7][8], lueco xylene cyanol FF [9], 2-ethylhexyl hydrogen 2-ethylhexyl phosphonate (KSM-17) [10], N, N'-Dimethyl-N,N'-diphenylpyridine-2, 6-dicarboxyamide (DMDPhPDA) [11], N-phenylbenzo-18-crown-6-hydroxamic acid [12], 1-octyl-3-methylimidazolium hexafluorophosphate [13], high molecular weight carboxylic acids [14], N -phenyl -(1,2-methanofullerene C 60 ) 61-formohydroxamic acid [15], tri-nbutyl phosphate (TBP) [16], tridodecylamine (TDA), 1-[thenoyl- (2)]-3-3-3-trifluoroacetone (HTTA), di (2-ethylhexyl) phosphoric acid (HDEHP) and tricaprylmethylammonium chloride (TCMA) [17], calyx [4] resorcinarene-N-fenil-acetohydroxamic acid [18], have been used for the extraction and separation of Ce(IV). However, these methods have limitations such as interference of different ions, emulsion formation, co-extraction, and use of high reagent concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The data given in [3] showed that at extraction of REEs with PhMDPA in chloroform their solvate numbers change from 3 (La) to 4 (Lu). Previously we have found [9] that the solvate number of europium determined from the curve slopes and by the saturation procedure comprises 2 and 2.5, respectively.…”
Section: Results and Disussionmentioning
confidence: 98%
“…It was found that extraction of americium with tetraalkyl-diamides of dipicolinic acid is nearly negligible [1]. Shimada et al [3] showed that dimethyldiphenyl-diamide of dipicolinic acid in chloroform exhibits rather high extraction capacity to rare-earth elements (REEs). The mixtures of diamides of dipicolinic acid with chlorinated cobalt dicarbollide (CCD) in meta-nitrobenzotrifloride (F3) or phenyltrifluoromethylsulfone (FS-13) efficiently extracted actinides and REEs from acidic solutions [4,5,6].…”
Section: Introductionmentioning
confidence: 98%
“…The extraction of An(III) and Ln(III) using diamide compounds is influenced by the structure of their coordination sites and the nature of the substituents on the amide nitrogen. Thus far, various diamide compounds consisting of some methylene groups and functional groups between amide groups and various substituents on the amide nitrogen have been researched and developed [1][2][3][4][5][6][7]. In our laboratory, N,N -dimethyl-N,N -diphenylpyridine-2,6-dicarboxyamide (DMDPhPDA), which possesses a pyridine ring between the amide groups and methyl and phenyl groups on the amide nitrogen, was synthesized; further, its extraction properties were investigated [6][7][8].…”
Section: Introductionmentioning
confidence: 99%